Attitudes and pro-environmental behaviours: determining factor of personality and lifestyle - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Hitam, Mizan (Malaysian Institute Of Planners, 2020)
Sustainability in well-being embodies the interconnecting course of how various systems influence each other. The more strongly individuals subscribe to values beyond their immediate interests, that is, prosocial, collectivistic and biospheric values, the more likely they are to engage in environmental behaviour. Issue: Existing research has limited evidence on specific values of Malaysian’s personality and lifestyle (PL) that have significant impact on attitude and proenvironmental behaviour (AP). Purpose: This paper aims to verify the statistical predictability of AP based on PL. Approach: Multiple Correlation and Multiple Linear Regression were carried out to assess linear associations and parameters of linear equations to predict AP components based on PL items. Findings: AP components were moderately predictable by some of the PL items. Specifically, ‘Urging media to raise environmental awareness’ and ‘being mindful about environmental destruction’ were the two strongest predictors of AP.